Pengaruh Harga Tandan Buah Sawit Terhadap Kesejahteraan Petani di Desa Beringin KecamatanTalang Muandau Kabupaten Bengkalis - Fuaddi, Husni; Bari, Rohmatul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The purpose of this study was to determine the effect of the price of palm fruit bunches on the welfare of farmers in Beringin Village, Talang Muandau District, Bengkalis Regency. The sample in this study were oil palm collectors and farmers in Beringin Village, Talang Muandau District, Bengkalis Regency totaling 30 people. While the variables examined in this study is the of price of palm fruit bunches and welfare of farmers. Based on the results obtained that price of palm fruit bunches simultaneously affect the welfare of farmers with a value of correlation R = 0.731 which shows the close relationship between the of price of palm fruit bunches and welfare of farmers in Beringin Village, Talang Muandau District, Bengkalis Regency. While the R-square at 0.535 which can mean of price of palm fruit bunches has a contribution of 53.5% contribution to welfare of farmers in Beringin Village, Talang Muandau District, Bengkalis Regency. Partially obtained of price of palm fruit bunches effect on the welfare of farmers in Beringin Village, Talang Muandau District, Bengkalis Regency with signifivantly 0.000 smaller than alpha 0.05. With simple linear regression equation in this study : Y = 7.008 + 0.809X.